Respostas
respondido por:
3
a)x² = 21² + 28²
x² = 441 + 784
x² = 1225
x =![\sqrt{1225} \sqrt{1225}](https://tex.z-dn.net/?f=+%5Csqrt%7B1225%7D+)
x = 35
b)11² = x² + 5²
x² = 11²-5²
x² = 121-25
x² = 96
x =![\sqrt{96} \sqrt{96}](https://tex.z-dn.net/?f=+%5Csqrt%7B96%7D+)
x = 9,79
c)![(x+1)^{2} =( \sqrt{7})^{2} + x^{2} (x+1)^{2} =( \sqrt{7})^{2} + x^{2}](https://tex.z-dn.net/?f=%28x%2B1%29%5E%7B2%7D++%3D%28+%5Csqrt%7B7%7D%29%5E%7B2%7D+%2B+x%5E%7B2%7D+)
x² + x + x+ 1 = 7 + x²
x² - x² + 2x = 8-1
2x = 7
x = 7/5
x² = 441 + 784
x² = 1225
x =
x = 35
b)11² = x² + 5²
x² = 11²-5²
x² = 121-25
x² = 96
x =
x = 9,79
c)
x² + x + x+ 1 = 7 + x²
x² - x² + 2x = 8-1
2x = 7
x = 7/5
VandersonPT:
vlw ✌
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás